Answer:
![\boxed{\sf \ \ f^(-1)(x)=(x-5)/(2) \ \ }](https://img.qammunity.org/2021/formulas/mathematics/college/o9tvsedidlsz2no59igmgbs0lmkjdyo3ld.png)
Explanation:
hello,
the easiest way to understand what we have to do is the following in my opinion
we can write
![(fof^(-1))(x)=x\\<=>f(f^(-1)(x))=x\\<=>2f^(-1)(x)+5=x\\<=>2f^(-1)(x)+5-5=x-5 \ \ \ subtract \ \ 5\\<=> 2f^(-1)(x)=x-5 \\<=> f^(-1)(x)=(x-5)/(2) \ \ \ divide \ by \ 2\\](https://img.qammunity.org/2021/formulas/mathematics/college/jnvf8grvop6856haxy1dio6rrwu1bbbvra.png)
so to follow the pattern of your question
y = 2x + 5
we need to find x as a function of y, so let's swap x and y
x = 2y + 5
then subtract 5
x - 5 = 2y
then divide by 2
![(x-5)/(2)=y](https://img.qammunity.org/2021/formulas/mathematics/college/pdeegvxs4budr6u6hnjzhlu6lqzug7mozu.png)
finally
![f^(-1)(x)=(x-5)/(2) \\](https://img.qammunity.org/2021/formulas/mathematics/college/pixg2yl1n4schnzg4r1m49oiq5gwwcvab6.png)
hope this helps